Implementation of Contextual Teaching and Learning Through The Exploration of Museum Mpu Purwa as A Social Studies Learning Resource - Nely Zulfatin Niamah; Mardhatillah Mardhatillah; Asyih Witayati (Jurnal Ilmiah Teunuleh, 2026)
Social studies education should link historical ideas with students' social and cultural backgrounds. Yet, teaching often focuses on textbooks and doesn't fully use resources near schools. This study examines how Contextual Teaching and Learning (CTL) is applied by using the Mpu Purwa Museum as a learning tool for seventh graders at SMPN 18 Malang. The study used a descriptive qualitative method, involving one social studies teacher, 31 students, and a museum guide. Data were gathered through participatory observation, in-depth interviews, document analysis, and learning materials like lesson plans, student worksheets, field notes, and student presentations. Data analysis included data condensation, thematic coding, data display, and drawing conclusions, with credibility ensured through source triangulation, technique triangulation, and member checking. The findings revealed that CTL was implemented in three integrated stages: planning, museum-based activities, and authentic assessment with reflection. The planning stage incorporated seven CTL components into the lesson design. The implementation stage included orientation, guide explanation, group observation, inquiry-based worksheet completion, presentation, and reflection. The evaluation stage used authentic assessment focusing on observation accuracy, artifact interpretation, collaborative discussion, presentation, and reflective meaning-making. The study concludes that the Mpu Purwa Museum can serve as a contextual, concrete, and culturally meaningful learning resource when museum exploration is intentionally aligned with CTL principles, curriculum goals, student inquiry, and reflective assessment.